2021
DOI: 10.2298/tsci190929468s
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of a novel low concentration dual photovoltaic/phase change material system with a non-concentrator photovoltaic system

Abstract: In this work, a novel design of a concentrated photovoltaic system with thermal management using phase change material is analyzed. The novelty lies in utilizing two mono-facial PV cells, installing one on upper side of the receiver to receive non-concentrated sunlight and installing another photovoltaic cell on bottom side to receive concentrated sunlight. An RT47 (melting range of 41-48℃) phase change material enclosed in an Aluminum containment regulates the temperature of the system. Parabolic trough conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The performance of a CPV system with RT47 as PCM was analyzed for the weather conditions of Doha, Qatar with CR of 25 [16]. It was observed that the PCM maintained the temperature of the PV cell below 85 °C for all months of a year.…”
Section: Figure 1 Different Thermal Management Approachesmentioning
confidence: 99%
“…The performance of a CPV system with RT47 as PCM was analyzed for the weather conditions of Doha, Qatar with CR of 25 [16]. It was observed that the PCM maintained the temperature of the PV cell below 85 °C for all months of a year.…”
Section: Figure 1 Different Thermal Management Approachesmentioning
confidence: 99%
“…The thermal efficiency of all selected PCMs in the CPVPCM system is calculated using Equation (10), and the result is shown in Figure 12. The analysis of the results has shown that the thermal efficiencies of salt and STL47 are better than all other PCM except in December which is due to their high latent heat of fusion.…”
Section: Thermal and Overall Efficiencymentioning
confidence: 99%
“…An indoor experimental study has shown an electrical efficiency improvement of 7.7% for a building-integrated CPVPCM system (geometrical concentration ratio of ~2.7) compared to a naturally ventilated CPV system [9]. In a theoretical study conducted for the environmental conditions of Doha (Qatar), a CPVPCM system (concentration ratio of 25) was able to produce power in the range of −4.7% to 21.7% as compared to a flat plate system while keeping the temperature of the system below 85 • C year round [10]. A 2D thermal model for an embedded CPV with a coupled thermo-fluids model for investigating the phase change phenomenon of PCM was presented in [11].…”
Section: Introductionmentioning
confidence: 99%
“…The inactive second method is used to resist the temperature raise of pv system this is containing phase change material for heat controlling [26,27]. The latent heat of mixture is absorbed by the pcm the surplus thermal energy of cell, in uniform temperature in which the phase transfer happens that resist efficiency reduction due to increment in temperature.…”
Section: G Phase Modification Substantialmentioning
confidence: 99%